2020
DOI: 10.1101/2020.02.29.971168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient opening of tricellular vertices controls paracellular transport through the follicle epithelium duringDrosophilaoogenesis

Abstract: Paracellular permeability is regulated to allow solute transport or migration of cells across epithelial or endothelial barriers. However, how occluding junction dynamics controls paracellular permeability is poorly understood. Here we describe patency, a developmentally regulated process in Drosophila oogenesis, during which cell vertices in the follicle epithelium open transiently to allow paracellular transport of yolk proteins for uptake by the oocyte. We show that the sequential removal of E-Cadherin, N-C… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…25 In contrast, most ectopic Col IV-GFP in Khc-73 cells is below the zonulae adherentes (ZAs), which demarcate lateral and apical domains (Figures 2A and 2B); there are not occluding junctions present while the BM is being made. [37][38][39] During the developmental stages when Col IV synthesis is high, ectopic extracellular Col IV-GFP accumulates all along the lateral domain in Khc-73 cells (Figures 2C-2E). As Col IV secretion ends, the ectopic Col IV becomes biased to an apical (upper) region of the lateral domain (Figure 2A), likely due to the movement of fibrils onto the BM that clears the basal (lower) regions of the lateral domain (Figure 2F).…”
Section: Khc-73 Biases Bm Protein Secretion To Basal Regionsmentioning
confidence: 99%
“…25 In contrast, most ectopic Col IV-GFP in Khc-73 cells is below the zonulae adherentes (ZAs), which demarcate lateral and apical domains (Figures 2A and 2B); there are not occluding junctions present while the BM is being made. [37][38][39] During the developmental stages when Col IV synthesis is high, ectopic extracellular Col IV-GFP accumulates all along the lateral domain in Khc-73 cells (Figures 2C-2E). As Col IV secretion ends, the ectopic Col IV becomes biased to an apical (upper) region of the lateral domain (Figure 2A), likely due to the movement of fibrils onto the BM that clears the basal (lower) regions of the lateral domain (Figure 2F).…”
Section: Khc-73 Biases Bm Protein Secretion To Basal Regionsmentioning
confidence: 99%
“…Prior studies indicate the presence of electron dense material between FE cells as early as stage 6 ( Müller 2000 ), with a ladder-like appearance of extracellular septa by stage 10B ( Mahowald 1972 ). A recent study of the occluding function in the FE shows a similar pattern of protein localization for endogenously tagged Neuroglian-YFP and Lachesin-GFP, and demonstrates that an intact occluding junction is formed during stage 11 of oogenesis ( Isasti-Sanchez et al 2021 ). It is interesting to note the FE is a secondary epithelium initiated by a mesenchymal to epithelial transition ( Tepass et al 2001 ), and yet SJ biogenesis appears to be very similar to that observed in the primary epithelia found in the embryo.…”
Section: Discussionmentioning
confidence: 78%
“…Prior studies indicate the presence of electron dense material between FE cells as early as stage 6 (Müller 2000), with a ladder-like appearance of extracellular septae by stage 10B (Mahowald 1972). A recent study of the occluding function in the FE show a similar pattern of protein localization for endogenously tagged Neuroglian-YFP and Lachesin-GFP, and demonstrates that an intact occluding junction is formed during stage 11 of oogenesis (Isasti-Sanchez et al 2020). It is interesting to note the FE is a secondary epithelium initiated by a mesenchymal to epithelial transition (Tepass et al 2001), and yet SJ biogenesis appears to be very similar to that observed in the primary epithelia found in the embryo.…”
Section: Biogenesis Of the Sj In The Fementioning
confidence: 86%